Formulasi Model Perkuliahan Daring Sebagai Upaya Menekan Disparitas Kualitas Perguruan Tinggi - Mokhamad Iklil Mustofa; Muhammad Chodzirin; Lina Sayekti; Roman Fauzan (Universitas Islam Negeri Walisongo Semarang, 2019)
A one-step using network technology and information technology for the development of learning system in universities is online lecturing system. This learning system is assessed as highly efficient, because the same learning resources can be used by hundred people at the same time. So, college student that lives in isolated area can access the subjects of reputable universities in Indonesia. Hence, the quality disparity of universities will be decreased.This study is qualitative descriptive research. The object of this study is on website pditt.belajar.kemdikbud.go.id. This website is developed by the Ministry of Education and Culture Indonesia. The selection of that locus is because the website is an official website of government which collaborate with some reputable universities in Indonesia, such as University of Indonesia, Bandung Institute of Technology, Gajahmada University, Sepuluh November Institut of Technology, Aptikom, and Bina Nusantara University.The result showed that online lecturing system has positive contribution for pushing the quality disparity of universities in Indonesia. The indications such as 1) Minimize the limitation of access to higher education that have a certain quality. 2) Cut-off the limitation of facilities that had been cosidered as one of obstacles of the lower quality of higher education. 3) Eliminate the limitation of understanding to certain material. 4) Online lecturing system gives wide access to educational resources, especially in reputable universities.